How the students' profile influences the english language competence at the intermediate intensive english I courses of the Foreign Language Deparment at the University of El Salvador - Flamenco Flamenco, Juan Antonio
This study was aimed at determining how students’ profile influences the development of their language competence. It was carried out in order to answer the question “How does students’ profile influence the English language competence at the Intermediate Intensive English I courses of the Foreign Language Department at the University of El Salvador?” In this research, three main aspects of students’ profile were taken into account: extracurricular activities, socio-economic status (SES), and motivation. To collect the data, the instrument selected was a questionnaire, and it was administered to 54 students. Having administered the questionnaires, the students’ profile was divided into advantaged and disadvantaged profile. The results showed that the students’ profile influences them when developing their language competence. This research supported that extracurricular activities influence students’ language competence when they were actively involved in them. This could be clearly reflected in their GPA, grade point average. All those students who were active religious members, active members of a neighborhood committee, or those who belonged to sports teams, or political parties got lower grade point averages than those who were not involved in one or any extracurricular activities.